2019
DOI: 10.17098/amj.542289
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Active Surveillance Practice in Registration and Monitoring of Tuberculosis Patients, in Ankara Province

Abstract: Tüberküloz (TB), dünyada yaklaşık her yıl 10 milyon kişide görülmektedir ve enfeksiyondan kaynaklanan ölümlerin başında yer almaktadır. Dünya genelinde 2017 yılı için, tahmin edilen vaka sayısı ile resmi rakamları oluşturan raporlanmış vakalar arasındaki 3,6 milyon hasta farkının yetersiz tanı ve eksik bildirimlerden kaynaklandığı düşünülmektedir. Türkiye'de ulusal TB programının temelini, hastaların erken bulunması ve etkili olarak tedavilerinin sağlanması oluşturmaktadır. Ülkemizde yasal olarak bildirimi zor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…A local study conducted in the capital city of Turkey demonstrated that the initiation of active surveillance activities led to a substantial increase in new cases. 17 Moreover, notifications may be limited by underascertainment due to not all cases seeking healthcare or by underreporting due to the failure of reporting cases. 18 - 20 Standardizing and strengthening contact tracing procedures at the provincial level would enhance case finding and thus TB notifications.…”
Section: Discussionmentioning
confidence: 99%
“…A local study conducted in the capital city of Turkey demonstrated that the initiation of active surveillance activities led to a substantial increase in new cases. 17 Moreover, notifications may be limited by underascertainment due to not all cases seeking healthcare or by underreporting due to the failure of reporting cases. 18 - 20 Standardizing and strengthening contact tracing procedures at the provincial level would enhance case finding and thus TB notifications.…”
Section: Discussionmentioning
confidence: 99%
“…2,12,13,16 Türkiye'de rutin aşılama programında yer alan BCG, şu anda TB'a karşı mevcut olan tek aşıdır ve küresel olarak her yıl 100 milyondan fazla BCG uygulanmaktadır. 3,25 BCG aşısı genellikle skar oluşumuna ve PPD reaksiyonuna yol açmaktadır. 16 Aşı yaygınlığı ve/veya etkinliği ile ilgili çalışmalarda, BCG aşısı skarının varlığı veya yokluğu, aşılama durumunun bir göstergesi olarak kullanılır.…”
Section: Sağlık öğRencilerinde Tüberküloz Prevalansıunclassified